Ensemble-based docking: From hit discovery to metabolism and toxicity predictions. Issue 20 (15th October 2016) - Evangelista, Wilfredo; Weir, Rebecca L.; Ellingson, Sally R.; Harris, Jason B.; Kapoor, Karan; Smith, Jeremy C.; Baudry, Jerome
Graphical abstract: Abstract: This paper describes and illustrates the use of ensemble-based docking, i.e., using a collection of protein structures in docking calculations for hit discovery, the exploration of biochemical pathways and toxicity prediction of drug candidates. We describe the computational engineering work necessary to enable large ensemble docking campaigns on supercomputers. We show examples where ensemble-based docking has significantly increased the number and the diversity of validated drug candidates. Finally, we illustrate how ensemble-based docking can be extended beyond hit discovery and toward providing a structural basis for the prediction of metabolism and off-target binding relevant to pre-clinical and clinical trials.